مساهمة في دراسة الينابيع تحت البحرية في الساحل السوري - شريف بدر حايك (Tishreen University, 2019)
يتضمن البحث التقييم الكمي والنوعي للينابيع تحت البحرية على الساحل السوري، وذلك بإجراء تحريات وقياسات بحرية، تترافق بقياسات سطح المياه الجوفية في آبار مراقبة محفورة في طبقة المياه الجوفية المضغوطة العائدة للكريتاسي، حيث تنصرف هذه المياه في البحر دون استثمار على شكل ينابيع تحت بحرية في مناطق تكشفاتها في البحر تبعاً للبنية الفالقية السائدة. تتفاوت سرعة جريان مياه الينابيع تحت البحرية بين 0,11-0,65 m/sec وتصاريفها بين ، تبعاً لفروق الكثافة والضاغط الهيدروليكي وسرعة الجريان بين مياه الينابيع تحت البحرية ومياه البحر. وتختلط مياه هذه الينابيع مع مياه البحر عند السطح لتشكل مياه جوفية تنحصر نسبة المياه العذبة فيها بين (20-90%) اعتماداً على الظروف الجيولوجية السائدة وحالتي الطقس والبحر. This research contains the quantitative and qualitative evaluations of the submarine springs in the Syrian Coast. The evaluation is carried out by making investigations and marine measurements of these springs, combined with measurements of the groundwater levels in the monitored wells, drilled in the cretaceous confined aquifer. This aquifer flows out into the sea without being exploited as submarine springs, according to the tectonic structure. The flow velocity of the submarine springs water is between 0,11-0,26 m/sec, and its discharges are , according to the differences involving density, hydraulic head, and flow velocity of the springs and sea water. The springs' water is mixed with the sea water on the surface, to form groundwater: 20 to 90% fresh water contents, according to the geological setting as well as climate and sea conditions.